Analysis of Hydroquinone Content in Whitening Cream Circulating in Gorontalo City Using Uv-Vis Spectrophotometry - Jauria; Kostiawan Sukamto; Ariani Hutuba (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the content of hydroquinone in whitening cream circulating in the city of Gorontalo and to determine the level of hydroquinone in bleaching cream circulating in the city of Gorontalo. This research method is a designmixed methods, which is a rare research by combining two forms of approach in research, namely qualitative and quantitative. This study began with a qualitative analysis using FeCl3 and Benedict's reagents so that the results were obtained that from 8 samples of whitening cream (A, B, C, D, E, F, G, H) there were 2 samples of whitening cream containing hydroquinone, namely cream A and C. then continued with a quantitative test using UV VIS spectrophotometry. The result is that sample A contains 41,976 mg/g and sample C 28,430 mg/g then proceeds with the validation of the analytical method, the validation parameters include linearity, limit of detection (LOD) and limit of quantification (LOQ). carried out with the value of the correlation coefficient R = 0.9999 and LOD = 18.642 PPM, LOQ = 62.142 PPM.